2020
DOI: 10.3390/ijerph17239044
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Minute Walk Test in Persons with Multiple Sclerosis: Correlations of Cadence with Free-Living Walking Do Not Support Ecological Validity

Abstract: The two-minute walk test (2MWT) is a frequently used walking capacity test in persons with multiple sclerosis (pwMS). However, less is known about its relevance with regards to walking capacity during free-living walking performance. Therefore, the ecological validity of the 2MWT was tested by 1. computing free-living minutes with the same intensity (cadence) as during the 2MWT and 2. investigating the relationship between 2MWT cadence and minutes with the same cadence during free-living walking. 20 pwMS aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…These results are consistent with Storm et al, who found that gait pace significantly increased and variability significantly decreased with increasing bout length [ 24 ]. Karle et al found little correlation between an in-lab 2-minute walk test and free-living walking [ 25 ]. In older adults, Najafi et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with Storm et al, who found that gait pace significantly increased and variability significantly decreased with increasing bout length [ 24 ]. Karle et al found little correlation between an in-lab 2-minute walk test and free-living walking [ 25 ]. In older adults, Najafi et.…”
Section: Discussionmentioning
confidence: 99%
“…However, deploying these models remotely comes with additional challenges that may impact model performance. For example, it is well established in PwMS [24][25][26] and other populations [27][28][29] that gait observed in the clinic differs from gait observed remotely (especially for gait speed-dependent variables). Similarly, studies in older adults [30] and PwMS [24] have also discovered that gait parameters change with walking bout duration.…”
Section: Introductionmentioning
confidence: 99%
“…Walk endurance tests are important to quantify walking parameters accurately [47,48]. Therefore, we applied two novel algorithm-based approaches using accelerator sensors in comparison to the current standard measurement using the odometer in the walking assessment of pwMS.…”
Section: Discussionmentioning
confidence: 99%
“…For this, the average cadences were processed from the raw acceleration data of an activity monitor. An average cadence between a clinical environment and an outside environment was compared [48]. Unfortunately, both studies did not include a gold standard of measurement to verify the respective measurement system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers and clinicians have typically adopted performance tests to assess physical function and mobility in MS [ 24 ]. However, there is evidence that performance-based tests may not present ecological validity [ 47 ]—these tests and outcomes may not totally reflect free-living performance, which entails unsupervised monitoring in the wild [ 48 ]. Conversely, wearable sensor technology in MS allows for the collection of free-living data that may serve as biomarkers of disease severity and progression.…”
Section: Opportunities For Using Motion Sensors In Msmentioning
confidence: 99%